CITRA WANITA TOKOH SELENA DALAM NOVEL SELENA KARYA TERE LIYE (KAJIAN PSIKOLOGI SASTRA) - Sumiharti Sumiharti; Dian Novita Sari. S (Universitas Batanghari, 2022)
This study aims to describe the woman image of Selena's character in Tere Liye's Selena Novel, which refers to psychological aspects, namely attitudes and levels of ingenuity in literary psychology study. This research uses qualitative descriptive methods. Qualitative descriptive definition is a type of research used to understand the phenomena experienced by the research subject by describing in the form of words and language using data from research results in novels. The data in the novel is in the form of excerpts from the aspects of attitude and level of ingenuity in Selena in Tere Liye's Selena Novel. Based on the results of this study, it can be concluded that the woman image of Selena’s character in the novel Selena by Tere Liye consists of 2 psychological aspects, namely the attitude aspect and the level of ingenuity.The attitude aspect is divided into two, a positive attitude and a negative attitude. Positive attitude, namely four quotes of friendly attitude, five of brave attitude, 14 of optimism attitude, ten of help attitude, and 6 of hardworking attitude. In addition, for the negative attitude, there are four quotes about stealing, seven about grumpy attitude, four about lying attitude, three about pessimistic attitude, and two about complaining attitude. Next, the aspects of the level of ingenuity are language intelligence/linguistics accounted for eight quotes, seven quotes of mathematical logic intelligence, one quote of intrapersonal intelligence, three quotes of interpersonal intelligence, one quote of musical or musical intelligence, one quote, three quotes of visual and spatial intelligence, and three quotes of kinesthetic intelligence. Thus the total the data is 85 Citations.